The Integrative Conjugative Element clc (ICEclc) of Pseudomonas aeruginosa JB2 - Obi, Chioma C.; Vayla, Shivangi; de Gannes, Vidya; Berres, Mark E.; Walker, Jason; Pavelec, Derek; Hyman, Joshua; Hickey, William J. (Frontiers in Microbiology, 2018)
Integrative conjugative elements (ICE) are a diverse group of chromosomally-integrated, self-transmissible mobile genetic elements (MGE) that are active in shaping the functions of bacteria and bacterial communities. Each type of ICE carries a characteristic set of core genes encoding functions essential for maintenance and self-transmission, and cargo genes that endow on hosts phenotypes beneficial for niche adaptation. An important area to which ICE can contribute beneficial functions is the biodegradation of xenobiotic compounds. In the biodegradation realm, the best-characterized ICE is ICEclc, which carries cargo genes encoding for ortho-cleavage of chlorocatechols (clc genes) and aminophenol metabolism (amn genes). The element was originally identified in the 3-chlorobenzoate-degrader Pseudomonas knackmussii B13, and the closest relative is a nearly identical element in Burkholderia xenovorans LB400 (designated ICEclc-B13 and ICEclc-LB400, respectively). In the present report, genome sequencing of the o-chlorobenzoate degrader Pseudomonas aeruginosa JB2 was used to identify a new member of the ICEclc family, ICEclc-JB2. The cargo of ICEclc-JB2 differs from that of ICEclc-B13 and ICEclc-LB400 in consisting of a unique combination of genes that encode for the utilization of o-halobenzoates and o-hydroxybenzoate as growth substrates (ohb genes and hyb genes, respectively) and which are duplicated in a tandem repeat. Also, ICEclc-JB2 lacks an operon of regulatory genes (tciR-marR-mfsR) that is present in the other two ICEclc, and which controls excision from the host. Thus, the mechanisms regulating intracellular behavior of ICEclc-JB2 may differ from that of its close relatives. The entire tandem repeat in ICEclc-JB2 can excise independently from the element in a process apparently involving transposases/insertion sequence associated with the repeats. Excision of the repeats removes important niche adaptation genes from ICEclc-JB2, rendering it less beneficial to the host. However, the reduced version of ICEclc-JB2 could now acquire new genes that might be beneficial to a future host and, consequently, to the survival of ICEclc-JB2. Collectively, the present identification and characterization of ICEclc-JB2 provides insights into roles of MGE in bacterial niche adaptation and the evolution of catabolic pathways for biodegradation of xenobiotic compounds.